2019
DOI: 10.14710/alj.v2i2.248-258
|View full text |Cite
|
Sign up to set email alerts
|

Kelemahan Lembaga Keberatan Pajak

Abstract: Tax disputes can occur between taxpayers or tax insurers with the government, among others because of differences in the amount of tax payable. One of the legal efforts that can be taken by taxpayers in the event of a tax dispute is an "Objection" legal effort. This objection is essentially a legal effort that is outside the Tax Court to appeal for justice in a tax dispute. The problem, what weaknesses are there in the objection institutions that exist today. Some of the weaknesses in this tax objection instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There have been several studies that have discussed the effectiveness and efficiency of tax dispute resolution in Indonesia. Ispiyarso (2019), for example, found several weaknesses in tax objection institutions in Indonesia. On the other hand, Aritonang (2020), identified the causes of DGT's loss in tax disputes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies that have discussed the effectiveness and efficiency of tax dispute resolution in Indonesia. Ispiyarso (2019), for example, found several weaknesses in tax objection institutions in Indonesia. On the other hand, Aritonang (2020), identified the causes of DGT's loss in tax disputes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings are shown in Table 2. Ispiyarso (2019) argues that the high percentage of decisions on rejecting tax objections indicates that the institution handling the objection is not independent of the taxpayers' perspectives.…”
Section: Statistical Data Of Decisions Of Tax Objectionmentioning
confidence: 99%
“…The tax objection decision can be in the form of the objection request being granted in a whole or a part (Rochaeti, 2012;Simandjuntak, 2014). DJP can also issue a decision in the form of completely rejecting the tax objection, even increasing the amount of tax to be paid (Asmorowati, 2011;Ispriyarso, 2019;Simandjuntak, 2014).…”
Section: Tax Audit Processmentioning
confidence: 99%
“…The tax court provides a decision on the appeal submitted by the taxpayer in accordance with the provisions of the Tax Court Law (Asriyani, 2017). Ispriyarso (2019) revealed that more than 40% of all appeals were granted by the Tax Court. If the tax appeal request is rejected or granted but only partially, the taxpayer is subject to administrative sanctions in the form of a fine of 100% of the total tax based on the appeal decision minus the amount of tax paid before filing an objection (Article 27, Law No.…”
mentioning
confidence: 99%
See 1 more Smart Citation